A Review of River Herring Science in Support of Species Conservation and Ecosystem Restoration. Issue 6 (3rd November 2021) - Hare, Jonathan A.; Borggaard, Diane L.; Alexander, Michael A.; Bailey, Michael M.; Bowden, Alison A.; Damon‐Randall, Kimberly; Didden, Jason T.; Hasselman, Daniel J.; Kerns, Toni; McCrary, Rachel; McDermott, Sean; Nye, Janet A.; et al.
Abstract: River herring—a collective name for the Alewife Alosa pseudoharengus and Blueback Herring A. aestivalis —play a crucial role in freshwater and marine ecosystems along the Eastern Seaboard of North America. River herring are anadromous and return to freshwater habitats in the tens to hundreds of millions to spawn, supplying food to many species and providing nutrients to freshwater ecosystems. After two and a half centuries of habitat loss, habitat degradation, and overfishing, river herring are at historic lows. In 2013, National Oceanic and Atmospheric Administration Fisheries established the Technical Expert Working Group (TEWG) to synthesize information about river herring and to provide recommendations to advance the science related to their restoration. This paper was composed largely by the chairs of the TEWG subgroups and represents a review of the current state of knowledge of river herring, with an emphasis on identification of threats and discussion of recent research and management actions related to understanding and reducing these threats. Important research needs are then identified and discussed. Finally, current knowledge is synthesized, considering the relative importance of different threats. This synthesis identifies dam removal and increased stream connectivity as critical to river herring restoration. Better understanding and accounting for predation, climate change, and fisheries are also important for restoration. Finally, there is recent evidence that the effects of human development and contamination on habitat quality may be more important threats than previously recognized. Given the range of threats, an ecosystem approach is needed to be successful with river herring restoration. To facilitate this ecosystem approach, collaborative forums such as the TEWG (renamed the Atlantic Coast River Herring Collaborative Forum in 2020) are needed to share and synthesize information among river herring managers, researchers, and community groups from across the species' range.